How possible is the elimination of viral hepatitis? An analysis based on the global burden of disease from hepatitis B and C, 1990–2019 (2024)
This study assesses the feasibility of hepatitis B (HBV) and C (HCV) elimination using an analysis of trends of epidemiology data (1990–2019) from the Global Burden of Disease Study. Joinpoint regression analysis was used to identify significantly changing points in the trends of Age-standardized Prevalence Rates (ASPR) and Age-standardized Mortality Rates (ASMR) and to estimate the annual percentage changes (APC) and the average annual percentage changes (AAPC) for the period. The Sociodemographic Index (SDI) was used to analyze trends between countries. The total percentage change of the ASPR (2019/1990) was −31.4% and −12.8% for HBV and HCV worldwide, respectively; the rate ratio (HBV/HCV) was 2.5. Mortality had decreased for HBV but not for HCV. The total percentage change for the ASMR (2019/1990) was −26.7% and 10.0% for HBV and HCV, respectively. While the ASMR of HBV decreased, HCV increased during this period. The percentage change in ASMR of HBV was highest in countries with high–middle SDI and lowest in countries with high SDI. For HCV, the percentage change in ASMR was highest in countries with high SDI (increase), and only in countries with low SDI did it decrease. The global HBV and HCV rates have fallen with different AAPCs associated with the SDI. Despite the advances, there is still a long way to go to achieve the 2030 elimination goals. An important challenge is related to finding a way to speed up the yearly rate at which the decline is happening